Autogenous vaccination reduces antimicrobial usage and mortality rates in a herd facing severe exudative epidermitis outbreaks in weaned pigs. (30th June 2018) - Arsenakis, Ioannis; Boyen, Filip; Haesebrouck, Freddy; Maes, Dominiek G D
Abstract : This study was conducted in a commercial 1000‐sow herd facing recurrent exudative epidermitis (EE) outbreaks during the nursery period and assessed the efficacy of autogenous vaccination in controlling such outbreaks. The vaccine was produced using three Staphylococcus hyicus isolates recovered from affected pigs shortly before the onset of the study. All of those isolates were positive for the exh B gene, which encodes the exfoliative toxin type B (ExhB). From four consecutive farrowing batches of sows, two batches were vaccinated (V) against S hyicus at five and two weeks before farrowing, and two sow batches remained non‐vaccinated (NV). Vaccination efficacy was primarily determined by the levels of metaphylactic antimicrobial usage, and the morbidity and mortality data for the pigs of the V and NV sows. The total amount of antimicrobials used metaphylactically against EE in pigs among the V and NV farrowing batches was 39, 600 and 88, 550 mg, respectively. The used daily dose pig to animal daily dose pig ratio for the V and NV batches were 1.31 and 1.79, respectively (a ratio of 0.8 to 1.2 is indicative of correct dosing). The morbidity and mortality rates were V=6.50 and NV=14.36 (P=0.008), and V=2.59 and NV=5.02 (P=0.000), respectively. To conclude, autogenous vaccination of the sows with a vaccine based on exh B‐positive S hyicus isolates reduced metaphylactic treatment with antimicrobials as well as the morbidity and mortality rates in weaned pigs compared with pigs from NV sow batches.